A retrospective study of mullerian anomalies and their outcome in pregnancy in a tertiary care center - Sai Lakshmi Shreya, Chinthala; Papanna, Rathnamma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Uterine abnormalities resulting from aberrant embryonic development, fusion, or resorption of the Mullerian ducts, the primitive homologue of the female reproductive tract, are known as congenital uterine malformations. In the reproductive age range, its prevalence is 2-4%, and in women who have had unfavourable reproductive outcomes, it is 5-25%. These deformities are linked to several obstetrical outcomes, including fetal growth limitation, fetal death, premature rupture of the membranes, preterm delivery, and a higher risk of ectopic pregnancy. They are also linked to first and second-trimester abortions. This study aimed to observe the different types of Mullerian anomalies and their outcome among pregnant women. Methods: A retrospective observational study was carried out in the Department of Obstetrics and Gynecology in tertiary care hospital from May 2022 to March 2024. Results: During this study, malpresentations found in bicornuate, unicornuate, didelphys uterus. Abortions were reported in 25% of cases. Conclusions: A high suspicion level should be maintained for patients presenting with infertility, repeated pregnancy loss, malpresentations, and a poor obstetric history. Early diagnosis and treatment will give better outcome among the cases who had recurrent abortions and infertility.